Tlingit canoes pulled up on beach by camp, Yakutat, Alaska, ca. 1894 - Tancred, Douglas
Tlingit encampment ca.1890-1898 seen from a distance. In foreground is water, beach with several canoes; in middleground is house, tents and fish racks. PH Coll 514.73